Prospective interventional study of tenofovir in pregnancy to prevent vertical transmission of hepatitis B in highly viremic women. Issue 3 (March 2017) - Sellier, Pierre O.; Maylin, Sarah; Berçot, Béatrice; Chopin, Dorothée; Lopes, Amanda; Simoneau, Guy; Evans, John; Delcey, Véronique; Bénifla, Jean-Louis; Simon, François; Bergmann, Jean-François
Abstract : Background: The risk of vertical transmission of hepatitis B virus (HBV) increases as maternal HBV DNA increase, despite serovaccination to newborns. Methods: From 1 July 2012 to 1 January 2016, all pregnant women in Lariboisiere Hospital, Paris, France, with HBV DNA of 5 log10 IU/ml and above were administered tenofovir from week 28 of pregnancy until delivery. HBV DNA was measured at months 1, 2 of tenofovir and at delivery. The newborns were serovaccinated, tested for hepatitis B surface antigen, hepatitis B core antibody (HBcAb)±HBV DNA, and hepatitis B surface antibody (HBsAb) when aged 9 months, and then 24 months. This study was registered inhttp://www.ClinicalTrials.gov (NCT02039362). Results: Thirty-one women gave birth to 37 newborns. Maternal HBV DNA at baseline was 8.23 log10 IU/ml and above in 12 pregnancies. The mean (median) HBV DNA were 4.4±1.2 (4.8), 3.3±1.7 (3.8), and 2.1±1.9 (2.0) log10 IU/ml at months 1, 2 of tenofovir and at delivery, respectively. Twenty-seven newborns were followed up: none of the 19 children aged 9 months or older was positive for hepatitis B surface antigen when aged 9 months; 14 children tested positive for HBcAb (probably transferred maternal antibodies, not found when aged 24 months) and for HBsAb without HBV DNA. Four of the 19 children showed HBsAb without HBcAb, the last being doubtful for HBcAb and HBsAb without HBV DNA. Eight newborns aged less than 9 months were not tested. Conclusion: Tenofovir from week 28 of pregnancy to highly viremic HBV women plus serovaccination to newborns could prevent chronic and past infection.